(untitled) (Global Journal of Science Frontier Research, 2023)
The aim of this study is to reflect on teacher training based essentially on the Didactic Anthropological Theory and on research aimed at studying the praxeological needs of teachers It is a qualitative study of a theoreticalbibliographical nature as it produces reflections based on our theoretical framework and research that deals with teacher training in the light of the Didactic Anthropological Theory Our reflections led us to consider teacher training didactic infrastructures for teacher training and the praxeological needs of the teacher In addition we took as an example one of the episodes from the experimental phase of Lobo s research 2019 which aimed to study the knowledge of plane analytic geometry that can be acquired by students teacher trainees from a Mathematics degree course in Bahia Brazil participating in supervised curricular internship classes who were involved in a training process based on a Study and Research Pathway The aim is to reflect on the complexity of building teaching praxeologies